2018
DOI: 10.18203/2394-6040.ijcmph20180416
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge attitude and practice of blood donation in Hail University

Abstract: Background: Medical students should be well educated about blood donation and its importance, and their knowledge reflects what will be transferred to the community. Thus, the aim of this study was to explore the knowledge, attitude, and practice of blood donations among medical students in Hail University. Methods: Three hundred medical students from 2nd to 6th grade participated in this self-administered questionnaire that included their demographic data, questions about their previous experience with blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…2 On average, high income countries have 9 times higher donation rate compared to low income countries. 3 During the last few decades, the number of active blood donors was decreased and couldn't meet the increased demands for blood transfusion. Also, most of donors are involuntary who came only for their relatives or friends and paid donors while those who usually donate are few.…”
Section: Introductionmentioning
confidence: 99%
“…2 On average, high income countries have 9 times higher donation rate compared to low income countries. 3 During the last few decades, the number of active blood donors was decreased and couldn't meet the increased demands for blood transfusion. Also, most of donors are involuntary who came only for their relatives or friends and paid donors while those who usually donate are few.…”
Section: Introductionmentioning
confidence: 99%
“…One previous study found that most respondents had sufficient knowledge about blood donation, among them more than 99% believed the importance of blood donation for the communities and about 30% of then has donated blood (Alsalmi et al, 2019). Another study conducted in Hail in 2017, showed that low awareness of participants on blood donation and most of them never donated blood previously; while students in medical field had a positive attitude of blood donation (Alanazi et al, 2018). Furthermore, another study conducted in the same region showed that three quarters of participants aware the risk of virus's transmission during blood donation.…”
Section: Medical Sciencementioning
confidence: 99%
“…A study was done in the Hail region in 2017 to investigate the knowledge, attitude, and practice (KAP) about blood donation among undergraduate medical students. The study discovered that awareness was low due to a lack of knowledge about blood donation and that only a few of them had donated blood; however, medical students had a positive attitude toward blood donation (Alanazi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%